2019
DOI: 10.1136/bmjopen-2019-029605
|View full text |Cite
|
Sign up to set email alerts
|

Association between caring for grandchildren and feelings of loneliness, social isolation and social network size: a cross-sectional study of community dwelling adults in Germany

Abstract: ObjectiveThe aim of this study was to examine whether there is an association between grandparental care and loneliness, social isolation and/or the size of an individual’s social network among community-based adults aged ≥40 years.MethodsCross-sectional data were drawn from a population-based sample of individuals aged ≥40 years living in the community in Germany. Loneliness was measured using a short version of the De Jong Gierveld Loneliness Scale. Social isolation was measured using a scale developed by Bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 51 publications
0
16
0
1
Order By: Relevance
“…Grandparents in Greece take care of their grandchildren to facilitate working mothers ( 115 ). Caring for a grandchild was shown to expand older people’s social network and to reduce loneliness ( 116 , 117 ). Restriction measures and isolation deprived older people of the opportunity to contribute to their family and therefore to retain the sense of a significant societal role and connectedness.…”
Section: Discussionmentioning
confidence: 99%
“…Grandparents in Greece take care of their grandchildren to facilitate working mothers ( 115 ). Caring for a grandchild was shown to expand older people’s social network and to reduce loneliness ( 116 , 117 ). Restriction measures and isolation deprived older people of the opportunity to contribute to their family and therefore to retain the sense of a significant societal role and connectedness.…”
Section: Discussionmentioning
confidence: 99%
“…33 Nonetheless, there are more positive aspects related to the intergenerational relationship between grandparents and grandchildren, an important factor was the emotional support which can be understood as the expression of affection, trust and affection through physical or gestural exchange, while the cognitive refers to the exchange of experiences and information about the family, permitting to understand situations. 7 Concerning the limitations of this review, the authors defined both inclusion and exclusion criteria, in which the gray literature was not included. Moreover, there was defined a 10-year period for sample selection and language restriction.…”
Section: Resultsmentioning
confidence: 99%
“…A second person was involved in determining the search strategy and also critically reviewed the results of the literature search. Two recent studies drawing on the German Ageing Survey found that undertaking grandchild caregiving was associated with an increase in the grandparent’s social network size [ 5 , 6 ], suggesting that providing grandchild care generates additional opportunities to make meaningful social connections as well as access social circles that might not otherwise be accessible. This aligns with the findings of a study exploring the effects of grandchild caregiving on health and life satisfaction, which suggested that the provision of auxiliary care to grandchildren can be a source of positive emotions, and can facilitate social connectivity [ 7 ].…”
Section: Viewpointmentioning
confidence: 99%
“…found that the provision of grandchild care was associated with lower loneliness scores among grandparents living in Taiwan, characterizing the provision of grandchild care as possible protective factor for older Taiwanese [ 8 ]. The cross-sectional study that found an extended social network among German grandparents, also found reduced loneliness and social isolation scores among those undertaking care of a grandchild [ 5 ]. However, the literature to date also points to gender differences in the experience of grandchild caregiving.…”
Section: Viewpointmentioning
confidence: 99%